2020
DOI: 10.1186/s12887-020-02306-3
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver dissatisfaction with their child’s participation in home activities after pediatric critical illness

Abstract: Background Pediatric critical care is often accompanied by a variety of functional impairments. Preliminary evidence suggests children’s participation in home activities has a slow trajectory post-pediatric intensive care unit (PICU) discharge, however, additional and more granular knowledge on specific problematic activities is needed to inform patient-centric rehabilitative care. The objectives of this study are to identify common home activities in which caregivers’ report dissatisfaction and to determine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Recent research indicates a significant positive effect of the number of participation-focused caregiver strategies on the relationship between school environmental supports and school participation attendance among children and youth with disabilities and those at risk ( 7 ). Similarly, a prior study of critically ill children revealed an effect of having participation-focused caregiver strategies on higher caregiver satisfaction with their child's home participation when combined with receiving pediatric re/habilitation services ( 8 ). Since these prior studies focused on home or school participation ( 7 , 8 ), the role that caregiver strategies play in supporting child and youth community participation is less understood.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent research indicates a significant positive effect of the number of participation-focused caregiver strategies on the relationship between school environmental supports and school participation attendance among children and youth with disabilities and those at risk ( 7 ). Similarly, a prior study of critically ill children revealed an effect of having participation-focused caregiver strategies on higher caregiver satisfaction with their child's home participation when combined with receiving pediatric re/habilitation services ( 8 ). Since these prior studies focused on home or school participation ( 7 , 8 ), the role that caregiver strategies play in supporting child and youth community participation is less understood.…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, a prior study of critically ill children revealed an effect of having participation-focused caregiver strategies on higher caregiver satisfaction with their child's home participation when combined with receiving pediatric re/habilitation services ( 8 ). Since these prior studies focused on home or school participation ( 7 , 8 ), the role that caregiver strategies play in supporting child and youth community participation is less understood. The community setting becomes increasingly important as children age and transition into adulthood ( 9 ), yet it presents more barriers and a smaller variety of strategies ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 94%
“…LeBlond and colleagues [20] recently reported that among children ≤ 4 years, family functioning was significantly associated with HRQOL among TBI or orthotic injury populations 6 months after injury. Lastly, when exploring the link between functional status and functional performance or HRQOL, the environment in which the child lives may be a mediating factor and has been associated with parents' satisfaction with their child's participation in daily life activities within the home 6 months after pediatric critical illness [21,22].…”
mentioning
confidence: 99%
“…Another single-center pediatric study showed that implementation of an early mobility protocol decreased rates of delirium (14). A secondary analysis of a two-center prospective pediatric cohort showed that parental satisfaction in their child’s activities of daily living at home increased when the child participated in PICU early mobilization (7). Outside of these few studies, data are limited on outcomes associated with early mobilization of critically ill children.…”
mentioning
confidence: 99%
“…Families prioritize functional over physiologic recovery Jessica M. LaRosa, MD 1 Sapna R. Kudchadkar, MD, PhD, FCCM [1][2][3] Rehabilitation Utilization in the PICU: A Complicated Picture* as the desired primary outcome of their child's PICU stay (6). As such, more than 50% of caregivers report dissatisfaction in their child's participation in activities of daily living after PICU hospitalization (7). Thus, actions to mitigate the negative functional sequelae of PICU survivorship are imperative.…”
mentioning
confidence: 99%